One‐Step Fabrication of Highly Customizable Porous Core–Shell Microspheres for the Construction of a 3D Physiologically Relevant Perivascular‐Endosteal Multi‐Microenvironment Model of Breast Cancer Bone Metastasis - Hong, Meiying; Wang, Guanxiong; Yang, Menghan; Liu, Hong; Huang, Haisen; Liu, Tiantian; Wang, Siping; Shen, Rui; He, Huatao; Li, Yi; Du, Ting; Hao, Xin; et al. (Advanced functional materials, 2025)
The 3D model of the perivascular‐endosteal multi‐microenvironment (PVM‐EM) is crucial for studying early stage breast cancer (BrCa) bone metastasis. However, existing models struggle to accurately represent the composition and spatial intricacies of multi‐microenvironments, limiting their ability to support cellular functional expression within these systems. Here, the nested aqueous two‐phase system emulsion as a template to develop a novel type of core‐shell microsphere for establishing the PVM‐EM 3D model is utilized. This model enables precise control over the chemical composition, macroporous structure, and cell localization. By adjusting these parameters in each microenvironment, it is successfully reconstructed the PVM with precise compartmentalized cell distribution in the microsphere core and a functional EM in the microsphere shell in one step. The outcomes indicate that the porous architecture and cell localization significantly enhance cell activity and function within the microenvironment. Importantly, this multi‐microenvironment model effectively encapsulates the key biological processes associated with bone colonization in early BrCa bone metastasis, including elevated cytokine expression, extensive angiogenesis within PVM, and significant inhibition of alkaline phosphatase expression within EM. This method paves the way for efficient and precise control of physiologically relevant PVM‐EM models, facilitating future preclinical research and drug screening for BrCa bone metastasis. Functional scaffolds are crucial for constructing perivascular‐endosteal multi‐microenvironment (PVM‐EM) 3D models. The first synthesis of customizable porous core‐shell hydrogel microspheres is presented, capable of independently modulating the chemical composition and physical architecture of distinct microenvironmental matrices, while precisely controlling cellular localization. These microspheres facilitate the development of physiologically relevant PVM‐EM models, effectively mimicking early stages of breast cancer bone colonization.